2022
DOI: 10.1021/acs.macromol.2c01719
|View full text |Cite
|
Sign up to set email alerts
|

Competing Effects of Cohesive Energy and Cross-Link Density on the Segmental Dynamics and Mechanical Properties of Cross-Linked Polymers

Abstract: To develop structure–property relationships for cross-linked thermosetting polymers, it is crucial to better understand key factors that control their segmental dynamics and macroscopic properties. Here, we employ a coarse-grained (CG) polymer model to systematically explore the combined effect of varying the cohesive energy (ε) and cross-link density (c) on the segmental relaxation time and mechanical properties for a model cross-linked glass-forming thermoset material. We find that increasing c increases bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
75
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(93 citation statements)
references
References 97 publications
18
75
0
Order By: Relevance
“…Furthermore, reduced fragility with increasing network topology (Figure b) nicely correlates with the reduced liquid heat capacity, Δ c p at T g (Figure ). We should mention here that the origin of the inverse proportionality of T g with fragility (increasing the cross-linking density causes an increase of T g and a simultaneous reduction in fragility) can be discussed in view of recent molecular dynamics simulations of segmental dynamics in cross-linked polymers. , The simulations revealed that increasing cross-linking density (by the presence of charged functional groups of highly polar cross-linking agents) can increase T g and at the same time reduce the fragility as observed experimentally. The origin of the effect could be traced to competing effects involving the cohesive interaction energy.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Furthermore, reduced fragility with increasing network topology (Figure b) nicely correlates with the reduced liquid heat capacity, Δ c p at T g (Figure ). We should mention here that the origin of the inverse proportionality of T g with fragility (increasing the cross-linking density causes an increase of T g and a simultaneous reduction in fragility) can be discussed in view of recent molecular dynamics simulations of segmental dynamics in cross-linked polymers. , The simulations revealed that increasing cross-linking density (by the presence of charged functional groups of highly polar cross-linking agents) can increase T g and at the same time reduce the fragility as observed experimentally. The origin of the effect could be traced to competing effects involving the cohesive interaction energy.…”
Section: Resultsmentioning
confidence: 66%
“…The origin of the effect could be traced to competing effects involving the cohesive interaction energy. Increasing the cross-link density can increase the cohesive interaction strength when the cross-linking agent is highly polar, which can lead to a decreasing fragility that counterbalances the normal fragility increase from the geometrical constraints of cross-linking. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirm in Figure 12 that B is highly correlated with ⟨u 2 ⟩, in qualitative agreement with both linear 103 and highly branched thermoset polymers. 66,104 Previous simulation observations on linear and thermoset polymers indicated roughly universal curves for B versus ⟨u 2 ⟩ for fixed values of cross-linking density 66 or fixed values of the cohesive interaction parameter 104 governing the strength of the polymer−polymer attractive interaction. However, when the data are examined in greater detail, it was found that the variation of these molecular parameters gives rise to a family of curves having nearly the same shape, but which are clearly distinct.…”
Section: Segmental Motion and Bulkmentioning
confidence: 99%
“…As with all polymer materials, properties related to glass formation play a central role in the design and characterization of materials suitable for their intended applications. While there have been a significant number of studies of glass formation in uncharged polymer materials, relatively little is known about glass formation in charged polymer materials and the oligomeric analog of these materials, ionic liquids. Correspondingly, fundamental studies of glass formation in charged, and “analog” uncharged polymer materials as a reference point, would clearly be of interest in the development of this class of materials.…”
Section: Introductionmentioning
confidence: 99%